Hairpins participating in folding of human telomeric sequence quadruplexes studied by standard and T-REMD simulations - Stadlbauer, Petr; Kührová, Petra; Banáš, Pavel; Koča, Jaroslav; Bussi, Giovanni; Trantírek, Lukáš; Otyepka, Michal; Šponer, Jiří (Nucleic acids research, 2015)
DNA G-hairpins are potential key structures participating in folding of human telomeric guanine quadruplexes (GQ). We examined their properties by standard MD simulations starting from the folded state and long T-REMD starting from the unfolded state, accumulating ∼130 μs of atomistic simulations. Antiparallel G-hairpins should spontaneously form in all stages of the folding to support lateral and diagonal loops, with sub-μs scale rearrangements between them. We found no clear predisposition for direct folding into specific GQ topologies with specific syn/anti patterns. Our key prediction stemming from the T-REMD is that an ideal unfolded ensemble of the full GQ sequence populates all 4096 syn/anti combinations of its four G-stretches. The simulations can propose idealized folding pathways but we explain that such few-state pathways may be misleading. In the context of the available experimental data, the simulations strongly suggest that the GQ folding could be best understood by the kinetic partitioning mechanism with a set of deep competing minima on the folding landscape, with only a small fraction of molecules directly folding to the native fold. The landscape should further include non-specific collapse processes where the molecules move via diffusion and consecutive random rare transitions, which could, e.g. structure the propeller loops.
Keywords: DNA; simulace molekulární dynamiky; G-kvadruplexy; kationty; Telomere; Cations; Humans; lidé; Molecular Dynamics Simulation; telomery; G-Quadruplexes; Oxytricha